2019
DOI: 10.3390/computation7020032
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Deformation of Pillar-Type Profiled Membranes and Its Effects on Flow and Mass Transfer

Abstract: In electro-membrane processes, a pressure difference may arise between solutions flowing in alternate channels. This transmembrane pressure (TMP) causes a deformation of the membranes and of the fluid compartments. This, in turn, affects pressure losses and mass transfer rates with respect to undeformed conditions and may result in uneven flow rate and mass flux distributions. These phenomena were analyzed here for round pillar-type profiled membranes by integrated mechanical and fluid dynamics simulations. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…In the ideal case of a uniform (along the whole channel) transmembrane pressure (TMP), a relatively simple chain of effects and consequences would be triggered: (a) Membrane/channel deformation; (b) changes in the friction coefficients in both fluid compartments with respect to those in the undeformed configuration; and, finally, (c) consequent changes in the solutions flow rates for any given inlet-to-outlet imposed pressure drop. Such TMP effects in ED and RED processes were documented in our previous studies [22,23], which revealed a significant influence of membrane deformation on the hydrodynamics and mass transfer in channels equipped with different profiled membranes.…”
Section: Motivation and Strategy Of The Present Studysupporting
confidence: 60%
See 3 more Smart Citations
“…In the ideal case of a uniform (along the whole channel) transmembrane pressure (TMP), a relatively simple chain of effects and consequences would be triggered: (a) Membrane/channel deformation; (b) changes in the friction coefficients in both fluid compartments with respect to those in the undeformed configuration; and, finally, (c) consequent changes in the solutions flow rates for any given inlet-to-outlet imposed pressure drop. Such TMP effects in ED and RED processes were documented in our previous studies [22,23], which revealed a significant influence of membrane deformation on the hydrodynamics and mass transfer in channels equipped with different profiled membranes.…”
Section: Motivation and Strategy Of The Present Studysupporting
confidence: 60%
“…equations expressing the channel's apparent permeability as a function of the transmembrane pressure and superficial velocity, as defined in Section 2.1. As discussed above, such equations can be derived from our previous 3-D mechanical-fluid dynamics investigation at the lower scale level of a unit cell [22,23]. The sign convention for TMP adopted in the present paper is consistent with that adopted in our previous work: TMP is positive if the concentrate channel is compressed and the diluate channel is expanded, whereas it is negative if the concentrate channel is expanded and the diluate channel is compressed.…”
Section: Computational Domain and Modelling Assumptionssupporting
confidence: 56%
See 2 more Smart Citations
“…Also at the macroscopic scale, a combination of fluid dynamics and mechanical simulations is applied by Battaglia et al [14] to investigate the effect of the transmembrane pressure in electro-membrane processes using round pillar type-profiled membranes. This study shows that the pressure that arises between the solutions flowing in alternate channels causes a slight deformation of the membrane, which may affect its mass transport properties.…”
mentioning
confidence: 99%